PROSPECTS FOR THE DEVELOPMENT OF MEDICINE IN UZBEKISTAN. - Akhmedov Ziyovuddin Nuriddin ugli (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: The development of medicine in Uzbekistan is a rich tapestry woven with centuries-old traditional methods of treatment, cultural influences and modern achievements in the field of health care. Located at the crossroads of ancient trade routes and proud of a diverse population with a deep history of medical knowledge, Uzbekistan has made significant progress in the field of medicine, combining tradition with modernity, improving health services and improving the health of the population.